Graphene oxide-functionalized nanocomposites promote osteogenesis of human mesenchymal stem cells via enhancement of BMP-SMAD1/5 signaling pathway. (October 2021) - Li, Zhong; Xiang, Shiqi; Lin, Zixuan; Li, Eileen N.; Yagi, Haruyo; Cao, Guorui; Yocum, Lauren; Li, La; Hao, Tingjun; Bruce, Katherine K.; Fritch, Madalyn R.; Hu, Huanlong; et al.
Abstract: Biomaterials that can harness the intrinsic osteogenic potential of stem cells offer a promising strategy to accelerate bone regeneration and repair. Previously, we had used methacrylated gelatin (GelMA)-based scaffolds to achieve bone formation from human mesenchymal stem cells (hMSCs). In this study, we aimed to further enhance hMSC osteogenesis by incorporating graphene oxide (GO)-based nanosheets into GelMA. In vitro results showed high viability and metabolic activities in hMSCs encapsulated in the newly developed nanocomposites. Incorporation of GO markedly increased mineralization within hMSC-laden constructs, which was further increased by replacing GO with silica-coated graphene oxide (SiGO). Mechanistic analysis revealed that the nanosheet enhanced the production, retention, and biological activity of endogenous bone morphogenetic proteins (BMPs), resulting in robust osteogenesis in the absence of exogenous osteoinductive growth factors. Specifically, the osteoinductive effect of the nanosheets was abolished by inhibiting the BMP signaling pathway with LDN-193189 treatment. The bone formation potential of the technology was further tested in vivo using a mouse subcutaneous implantation model, where hMSCs-laden GO/GelMA and SiGO/GelMA samples resulted in bone volumes 108 and 385 times larger, respectively, than the GelMA control group. Taken together, these results demonstrate the biological activity and mechanism of action of GO-based nanosheets in augmenting the osteogenic capability of hMSCs, and highlights the potential of leveraging nanomaterials such as GO and SiGO for bone tissue engineering applications.